Ceramic / high-entropy alloy composite particle reinforced aluminum-based composite material and laser additive manufacturing method thereof
By using ceramic/high-entropy alloy composite particles as reinforced phases in aluminum-based composite materials and using laser selection melting technology, the poor bonding and reaction problems of ceramic particles and high-entropy alloy particles in aluminum-based composite materials are solved, and the problem of poor combination and reaction of ceramic particles and high-entropy alloy particles in aluminum-based composite materials is achieved. Improved mechanical properties and improved density of aluminum alloys.
Patent Information
- Application Number
- CN202411065604.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-05
AI Technical Summary
When the ceramic particles are enhanced, there are poor interfacial bonding, large internal stress and reaction problems, resulting in a decrease in plasticity. In addition, high-entropy alloys may react with the aluminum matrix during the SLM forming process to form brittle intermetallic compounds, resulting in pores. .
Ceramic/high-entropy alloy composite particles are used as reinforced phases to prepare aluminum-based composite materials through laser selection melting technology. The ceramic particles and high-entropy alloy particles are uniformly distributed, and the mass fraction of ceramics are between 0.5% and 50%, and the mass fraction of high-entropy alloys are The two form spherical composite powder at 50% to 99.5%, and then form in SLM technology after ball milling and mixing.
It improves the mechanical properties and density of aluminum alloys, suppresses adverse reactions between high-entropy alloys and aluminum matrix, reduces residual stress, forms a good intermetallic interface combination, and enhances the application range of composite materials.
Smart Images

Figure CN119140841A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal materials, and in particular relates to an aluminum-based composite material reinforced with ceramic / high-entropy alloy composite particles and a laser additive manufacturing method thereof. Background Art
[0002] Aluminum-based composites combine the advantages of aluminum alloys (low density, high ductility) and reinforcement materials (high strength, high elastic modulus), and have superior specific strength, high specific stiffness, low thermal expansion coefficient, and excellent wear resistance. Selective laser melting (SLM), as a type of additive manufacturing technology, has the characteristics of rapid heating and cooling, high precision, and high design freedom. When preparing aluminum-based composites, the unique Marangoni effect inside the molten pool can make the reinforcement phase evenly distributed inside the aluminum matrix. However, at present, single ceramic particles as reinforcement phases often produce sharp interfaces, resulting in large internal stresses in the aluminum matrix, and the interface bonding between ceramic particles and aluminum matrix is poor, and harmful reactions are prone to occur at the interface, resulting in a significant decrease in the plasticity of the composite material.
[0003] High Entropy Alloys (HEAs) have excellent mechanical properties. Compared with ceramic materials, HEAs have better wettability with aluminum matrix and higher interface bonding strength, and are very promising reinforcement materials. However, high entropy alloys are composed of multiple elements. During the SLM forming process, some elements may react with the aluminum matrix to form brittle intermetallic compounds, and pores are generated inside the aluminum matrix during the reaction.
[0004] Ceramic / high entropy alloy composite particles have the advantages of both ceramic particles and high entropy alloy particles. They have excellent mechanical properties and maintain good wettability and interface bonding with aluminum, and are not prone to reaction or decomposition. At present, there have been reports on the direct use of ceramic / high entropy alloy composite particles to prepare ceramic reinforced high entropy alloy composite materials through spark plasma sintering, hot pressing sintering, SLM and other technologies, but there have been no reports on the use of ceramic / high entropy alloy composite particles as a reinforcement phase to prepare aluminum-based composite materials. Therefore, in order to further improve the mechanical properties and application range of aluminum alloys, it is of great research significance and application value to explore a high-performance ceramic / high entropy alloy composite particle reinforced aluminum-based composite material and its laser additive manufacturing method. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies in the design theory of particle-reinforced aluminum-based composite materials and the preparation and forming process of industrial complex-shaped composite materials in the prior art, the primary purpose of the present invention is to provide a laser selective melting preparation process for ceramic / high-entropy alloy composite particle-reinforced aluminum-based composite materials.
[0006] Another object of the present invention is to provide a composite powder of ceramic / high entropy alloy composite particles reinforced aluminum alloy required for the above-mentioned preparation process.
[0007] Another object of the present invention is to provide an aluminum-based composite material reinforced with ceramic / high entropy alloy composite particles obtained by using the above-mentioned preparation process and composite powder.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A ceramic / high entropy alloy composite particle reinforced aluminum-based composite material and a laser additive manufacturing method thereof, wherein the material composition is characterized in that the matrix is various aluminum alloys, including cast aluminum alloys, such as Al-Si series, Al-Cu series, Al-Mg series, Al-Zn series; and also includes deformed aluminum alloys, such as 1xxx, 2xxx, 4xxx, 5xxx, 6xxx, 7xxx, alloys and Al-Li alloys. The reinforcing phase is ceramic / high entropy composite powder particles, wherein the ceramic particles include TiB2, TiC, TiN, SiC, ZrO2, etc.; the high entropy alloy particles include high entropy alloys such as FeCoCrNi series, FeCoCrNiMn series, FeCoCrNiMo series, AlCoCrFeNi series, AlTiCrNiCu series, WTaMoNbV series, TiNbZrTa series, etc.
[0010] Further, in the plasma spheroidized ceramic / high entropy alloy composite particle reinforcement phase, the mass fraction of ceramic is between 0.5% and 50%, the mass fraction of high entropy alloy is between 50% and 99.5%, and the sum of the two is equal to 1. The ceramic powder is flaky or other irregular shapes with a particle size of 0.05 to 1 μm, and the high entropy alloy powder is spherical with a particle size of 1 to 100 μm. The ceramic / high entropy alloy composite powder is spherical, has good fluidity and a particle size of 1 to 100 μm.
[0011] Furthermore, in the composite powder of ceramic / high entropy alloy composite particles reinforced aluminum alloy, the mass fraction of the ceramic / high entropy alloy composite particle reinforcement phase is 1% to 10%, the mass fraction of the aluminum alloy matrix is 90% to 99%, and the sum of the two is equal to 1, and the aluminum alloy powder is spherical and the particle size is between 1 and 100 μm.
[0012] A ceramic / high entropy alloy composite particle reinforced aluminum-based composite material and a laser additive manufacturing method thereof, wherein the preparation and forming process is characterized by: weighing ceramic / high entropy alloy composite powder and aluminum alloy powder for ball milling and mixing; and adopting laser selective melting technology to form and prepare the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material. The preparation process of the present invention is shown in the attached figure. Figure 1 shown.
[0013] The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material of the present invention specifically comprises the following steps:
[0014] (1) Preparation of composite powder: Weigh a certain mass fraction ratio of ceramic / high entropy alloy composite powder and aluminum alloy powder respectively, mix them evenly in a ball mill for 4 to 8 hours, and pass argon or nitrogen as protection. After sieving through a standard sieve, dry them in a vacuum environment at 70 to 120°C for 4 to 6 hours to obtain a composite powder of ceramic / high entropy alloy composite particles reinforced with aluminum alloy.
[0015] (2) Preparation of aluminum-based composite materials by SLM (Selective Laser Melting, SLM): The composite powder of ceramic / high entropy alloy composite particles reinforced aluminum alloy is spread on the substrate of the SLM metal 3D printer forming chamber, and the aluminum alloy substrate is preheated to 150-200°C under the condition of protective gas; the laser power is adjusted to 270-370 W and the scanning speed is adjusted to 1100 mm / s-1600 mm / s, the powder layer thickness is 20-75 μm, the scanning interval is 110-150 μm, and the scanning strategy is a 67° interlayer rotation; the laser is scanned layer by layer on the powder bed to deposit and form, and the aluminum-based composite material is printed.
[0016] A ceramic / high entropy alloy composite particle reinforced aluminum-based composite material is prepared by the above laser selective melting process.
[0017] The present invention proposes for the first time to use a high entropy alloy reinforced with ceramic particles as a reinforcement phase, which has the advantages of both a ceramic particle reinforcement phase and a high entropy alloy particle reinforcement phase. First, the laser absorption rate of the aluminum alloy can be effectively improved during the laser forming process. In addition, the ceramic / high entropy alloy composite particles can be evenly distributed inside the aluminum alloy matrix under the Marangoni effect in the molten pool, and have good wettability with the aluminum matrix to form a good metal-metal interface bond, making the composite material highly dense. Therefore, the ceramic / high entropy alloy composite particles can effectively improve the mechanical properties of aluminum-based composite materials, and can be used for the manufacture of high-performance complex parts such as aerospace, automobile rail transportation, etc.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0019] (1) In the ceramic / high entropy alloy composite powder of the present invention, nano-ceramics are distributed inside and on the surface of the high entropy alloy, and the composite powder has a high sphericity, a smooth surface, and good fluidity, which meets the requirements of the SLM technology for the powder used.
[0020] (2) The ceramic / high entropy alloy composite particle reinforced aluminum alloy composite powder of the present invention can improve the laser absorption rate of the aluminum-based composite material during the SLM forming process. The presence of the high melting point ceramic absorbs the energy required for the reaction between the high entropy alloy and aluminum, inhibits the adverse reaction between the high entropy alloy elements and the aluminum matrix, and reduces the porosity inside the matrix, thereby achieving a high density of the composite material and effectively improving the forming quality of the aluminum alloy.
[0021] (3) The ceramic / high entropy alloy composite particle reinforcement phase of the present invention is uniformly distributed inside the matrix, and presents an irregular shape or spherical shape under the action of the Marangoni effect in the molten pool, giving full play to the good wettability of the high entropy alloy and the aluminum matrix. No defects are observed at the interface, indicating that the metal bonding at the interface is good; a very thin transition layer is formed between the ceramic / high entropy alloy composite particle reinforcement phase and the aluminum matrix, and the load can be effectively transferred to the ceramic / high entropy composite particle reinforcement phase, reducing the residual stress in the SLM forming process and delaying the fracture of the aluminum-based composite material.
[0022] (4) The ceramic / high entropy alloy composite particles of the present invention have excellent strength and deformation capacity, and dispersedly distributed in the aluminum matrix can hinder the movement of dislocations and grain boundaries, and play the role of dislocation strengthening, grain boundary strengthening and dispersion strengthening; in addition, part of the ceramic and the aluminum matrix can form a strong nucleating agent, which can promote heterogeneous nucleation inside the aluminum alloy and refine the grains on the one hand, and on the other hand, the precipitation of nano-ceramics at the grain boundaries can also hinder the movement of grain boundaries and play a strengthening role. The aluminum-based composite material of the present invention has excellent mechanical properties and can be well applied in actual working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention provides a process flow chart for preparing the aluminum-based composite material reinforced with ceramic / high entropy alloy composite particles by laser selective melting.
[0024] Figure 2 This is a microscopic image of the aluminum-based composite material prepared in Example 1 of the present invention.
[0025] Figure 3 This is a microstructure morphology diagram of the aluminum-based composite material prepared in Example 1 of the present invention.
[0026] Figure 4 This is the microstructure morphology of AlSi10Mg prepared in the comparative example of the present invention. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. The embodiments listed below are only some embodiments of the present invention, and it should be understood that the protection scope of the present invention is not limited thereto.
[0028] Example 1
[0029] Step (1) Preparation of composite powder: The selected ceramic powder is TiB2 with an average particle size of 0.8 μm, the high entropy alloy powder is FeCoCrNi with an equiatomic ratio and a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm. First, FeCoCrNi high entropy powder and TiB2 ceramic powder are plasma spheroidized at a mass ratio of 95:5 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of ceramic / high entropy alloy composite powder and aluminum alloy powder are weighed, wherein the ceramic / high entropy alloy composite powder is 100% by mass and the aluminum alloy powder is 100% by mass. The mass fraction of the porcelain / high entropy alloy composite powder is 2%, and the rest is AlSi10Mg powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 4 hours. Argon is filled for protection at a rotation speed of 220rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiB2 / FeCoCrNi composite particles reinforced AlSi10Mg with a particle size of 15 to 53μm.
[0030] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 6061 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1400mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0031] The prepared aluminum-based composite materials were subjected to microstructure characterization, hardness testing, and room temperature tensile mechanical property testing that met national standards, such as Figure 2 , irregularly shaped or spherical ceramic / high entropy alloy composite particle reinforcement phases are evenly distributed inside the aluminum matrix. Figure 3 It is shown that the ceramic / high entropy alloy composite particles are well bonded to the aluminum matrix interface. Comparing the tensile properties of Example 1 with those of Comparative Example 1, it is found that the yield strength and tensile strength of the aluminum-based composite material are greatly improved, to 358.42MPa and 506.38MPa, respectively, the plasticity is maintained at 4.4%, and the hardness is also increased to 186.92HV.
[0032] Example 2
[0033] Step (1) Preparation of composite powder: The selected ceramic powder is TiB2 with an average particle size of 0.5 μm, the high entropy alloy powder is AlCoCrFeNi2.1 with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm. First, the AlCoCrFeNi2.1 high entropy powder and the TiB2 ceramic powder are plasma spheroidized in a mass ratio of 95:5 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of the ceramic / high entropy alloy composite powder and the aluminum alloy powder are weighed, wherein the ceramic / high entropy alloy composite powder and the aluminum alloy powder are The mass fraction of the porcelain / high entropy alloy composite powder is 2%, and the rest is AlSi10Mg powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 6 hours. Argon is filled for protection at a speed of 200 rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiB2 / AlCoCrFeNi2.1 composite particles reinforced AlSi10Mg with a particle size of 15 to 53 μm.
[0034] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 5083 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1400mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0035] The prepared aluminum-based composite material was subjected to microstructural characterization, hardness testing, and room temperature tensile mechanical properties testing that meets national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 362.39MPa and 517.32MPa respectively, the plasticity was maintained at 4.1%, and the hardness was also increased to 196.92HV. Figure 2 It was found that the particles were evenly distributed in the matrix and the interface was well bonded.
[0036] Example 3
[0037] Step (1) Preparation of composite powder: The selected ceramic powder is TiC with an average particle size of 0.5 μm, the high entropy alloy powder is FeCoCrNiMn with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm. First, FeCoCrNiMn high entropy powder and TiC ceramic powder are plasma spheroidized in a mass ratio of 95:5 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of ceramic / high entropy alloy composite powder and aluminum alloy powder are weighed, wherein the ceramic / high entropy alloy composite powder is 1.5 μm, and the aluminum alloy ... The mass fraction of the entropy alloy composite powder is 10%, and the rest is AlSi10Mg powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 10:1. They are added to a ball mill and mixed for 6 hours. Argon is filled for protection at a rotation speed of 180 rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiC / FeCoCrNiMn composite particles reinforced with AlSi10Mg with a particle size of 15 to 53 μm.
[0038] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 6061 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1300mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0039] The prepared aluminum-based composite material was subjected to microstructure characterization, hardness test and room temperature tensile mechanical property test that meets the national standard. It can be clearly found that the yield strength and tensile strength are greatly improved, increasing to 370.63MPa and 540.68MPa respectively, the plasticity is maintained at 3.3%, and the hardness is also increased to 200.34HV. Figure 2 Similar) found that there were no obvious defects within the organization.
[0040] Example 4
[0041] Step (1) Preparation of composite powder: The selected ceramic powder is TiC with an average particle size of 0.5 μm, the high entropy alloy powder is FeCoCrNiMo with a particle size of 15 to 53 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm. First, FeCoCrNiMo high entropy powder and TiC ceramic powder are plasma spheroidized in a mass ratio of 90:10 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of ceramic / high entropy alloy composite powder and aluminum alloy powder are weighed, wherein the ceramic / The mass fraction of the high entropy alloy composite powder is 3%, and the rest is AlSi10Mg powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 6 hours. Argon is filled for protection at a rotation speed of 160 rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiC / FeCoCrNiMo composite particles reinforced with AlSi10Mg with a particle size of 15 to 53 μm.
[0042] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 5083 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1500mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0043] The prepared aluminum-based composite material was characterized by microstructure and tested for room temperature tensile mechanical properties that meet national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 361.42MPa and 512.68MPa respectively, the plasticity was maintained at 3.8%, and the hardness was also increased to 192.6HV. Figure 2 It was found that the interface between the reinforcement phase and the matrix was smooth and clean.
[0044] Example 5
[0045] Step (1) Preparation of composite powder: The selected ceramic powder is ZrO2 with an average particle size of 0.5 μm, the high entropy alloy powder is TiNbZrTa with a particle size of 1 to 25 μm, and the aluminum alloy powder is 2024 series aluminum alloy with a particle size of 15 to 53 μm. First, the TiNbZrTa high entropy powder and the ZrO2 ceramic powder are plasma spheroidized in a mass ratio of 95:5 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of the ceramic / high entropy alloy composite powder and the aluminum alloy powder are weighed, wherein the ceramic / The mass fraction of the high entropy alloy composite powder is 2%, and the rest is 2024 aluminum alloy powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 4 hours. Argon is filled for protection at a rotation speed of 140rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of ZrO2 / TiNbZrTa composite particles reinforced with 2024 aluminum alloy with a particle size of 15 to 53μm.
[0046] Step (2): Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 2024 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 350W, scanning speed is 1600mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0047] The prepared aluminum-based composite material was characterized by microstructure and tested for room temperature tensile mechanical properties that meet national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 261.28MPa and 414.39MPa respectively, the plasticity remained at 9.3%, and the hardness was also increased to 143.68HV. Figure 2 It was found that the reinforcement phase was evenly distributed inside the matrix and the grains were refined.
[0048] Example 6
[0049] Step (1) Preparation of ceramic / high entropy alloy composite particle reinforced aluminum alloy composite powder: The selected ceramic powder is TiB2 with an average particle size of 0.1 μm, the high entropy alloy powder is AlCoCrFeNi2.1 with a particle size of 15 to 53 μm, and the aluminum alloy powder is 2024 series aluminum alloy with a particle size of 15 to 53 μm. First, AlCoCrFeNi2.1 high entropy powder and TiB2 ceramic powder are prepared by plasma spheroidization in a mass ratio of 50:50 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of ceramic / high entropy alloy composite powder is weighed. and aluminum alloy powder, of which the mass fraction of ceramic / high entropy alloy composite powder is 2%, and the rest is 2024 aluminum alloy powder. The sizes of stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 8h. Argon is filled for protection at a rotation speed of 200rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4h to obtain a spherical composite powder of TiB2 / AlCoCrFeNi2.1 composite particles reinforced with 2024 aluminum alloy with a particle size of 15 to 53μm.
[0050] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 2024 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1400mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0051] The prepared aluminum-based composite material was characterized by microstructure and tested for room temperature tensile mechanical properties that meet national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 270.3MPa and 425.65MPa respectively, the plasticity was maintained at 7.3%, and the hardness was also increased to 148.7HV. Figure 2 It was found that the particles were evenly distributed in the matrix without obvious defects.
[0052] Example 7
[0053] Step (1) Preparation of composite powder: The selected ceramic powder is TiB2 with an average particle size of 0.5 μm, the high entropy alloy powder is AlTiCrNiCu with a particle size of 15 to 53 μm, and the aluminum alloy powder is 2024 series aluminum alloy with a particle size of 15 to 53 μm. First, AlCoCrFeNi2.1 high entropy powder and TiB2 ceramic powder are prepared by plasma spheroidization in a mass ratio of 80:20 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of ceramic / high entropy alloy composite powder and aluminum alloy powder are weighed, wherein The mass fraction of the ceramic / high entropy alloy composite powder is 4%, and the rest is 2024 aluminum alloy powder. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 8 hours. Argon is filled for protection at a speed of 200 rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiB2 / AlTiCrNiCu composite particles reinforced with 2024 aluminum alloy with a particle size of 15 to 53 μm.
[0054] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 2024 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1400mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0055] The prepared aluminum-based composite material was characterized by microstructure and tested for room temperature tensile mechanical properties that meet national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 262.78MPa and 420.45MPa respectively, the plasticity remained at 5.82%, and the hardness was also increased to 151.23HV. Figure 2 It was found that the particles and the matrix interface were well bonded, showing a smooth and clean interface.
[0056] Example 8
[0057] Step (1) Preparation of composite powder: The selected ceramic powder is TiN with an average particle size of 0.5 μm, the high entropy alloy powder is AlCoCrFeNi2.1 with a particle size of 1 to 25 μm, and the aluminum alloy powder is AlSi10Mg with a particle size of 15 to 53 μm. First, the AlCoCrFeNi2.1 high entropy powder and the TiN ceramic powder are plasma spheroidized in a mass ratio of 95:5 to obtain a ceramic / high entropy alloy composite powder; then a certain mass ratio of the ceramic / high entropy alloy composite powder and the aluminum alloy powder are weighed, wherein the ceramic / high entropy alloy composite powder and the aluminum alloy powder are The mass fraction of the porcelain / high entropy alloy composite powder is 1%, and the rest is AlSi10Mg. The sizes of the stainless steel balls used are 2mm, 4mm, and 6mm. The stainless steel balls are weighed at a mass ratio of 3:2:1, and the ball-to-material ratio is 5:1. They are added to a ball mill and mixed for 6 hours. Argon is filled for protection at a rotation speed of 140 rpm. After that, they are sieved through a sieve and dried at 80°C in a vacuum drying oven for 4 hours to obtain a spherical composite powder of TiN / AlCoCrFeNi2.1 composite particles reinforced with AlSi10Mg with a particle size of 15 to 53 μm.
[0058] Step (2) Spread the composite powder in step (1) onto the substrate of the SLM metal printer forming cylinder. In this example, the substrate is a 5083 aluminum alloy plate, which is preheated to 200°C and filled with argon for protection. Use Solid Works software to perform 3D modeling, import the modeling into the equipment, and set the printing process parameters: laser power is 330W, scanning speed is 1400mm / s, powder layer thickness is 30μm, scanning spacing is 150μm, and the scanning strategy is 67° interlayer rotation.
[0059] The prepared aluminum-based composite material was characterized by microstructure and tested for room temperature tensile mechanical properties that meet national standards. It can be clearly found that the yield strength and tensile strength were greatly improved, increasing to 356.29MPa and 499.56MPa respectively, the plasticity was maintained at 4.6%, and the hardness was also increased to 170.32HV. Figure 2 It was found that the reinforcement phase was dispersed inside the aluminum matrix.
[0060] Comparative Example
[0061] In this comparative example, an AlSi10Mg alloy is prepared, which is different from Examples 1, 2, 3, 4, 5, and 8 in that no ceramic / high entropy alloy composite particle reinforcement phase is added, and the printing process is consistent.
[0062] Figure 4The microstructures perpendicular to the construction direction (a) and parallel to the construction direction (b) are typical of the comparative example. The microstructures perpendicular to the construction direction show α-Al and eutectic silicon distributed in a network, and the microstructures parallel to the construction direction show columnar crystals growing perpendicular to the molten pool. The addition of ceramic / high entropy alloy composite particle reinforcement phase can refine the grains to a certain extent, and the columnar crystals parallel to the construction direction are partially transformed into equiaxed crystals, which reduces the mechanical anisotropy of the composite material, and has a certain plasticity while improving the mechanical properties.
[0063] The mechanical properties of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite materials prepared in Examples 1, 2, 3, 4, and 8 are greatly improved compared to AlSi10Mg, while maintaining good plasticity.
[0064] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A laser additive manufacturing method for ceramic / high entropy alloy composite particles reinforced aluminum-based composite materials, characterized in that: The following steps are involved: (1) Preparation of composite powder: Weigh ceramic / high entropy alloy composite powder and aluminum alloy powder respectively, mix them evenly by ball milling, pass protective gas, sieve through a standard sieve and dry to obtain a composite powder of ceramic / high entropy alloy composite particles reinforced with aluminum alloy; (2) SLM preparation of aluminum-based composite materials: The composite powder of ceramic / high-entropy alloy composite particles reinforced aluminum alloy is spread flat on the substrate of the SLM metal 3D printer forming chamber, the substrate is preheated under the condition of protective gas, and the laser power, scanning speed, scanning spacing and powder layer thickness are adjusted so that the laser scans and deposits layer by layer on the powder bed to print out the aluminum-based composite material.
2. According to the laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material is characterized in that: The aluminum alloy includes a cast aluminum alloy, a deformed aluminum alloy or an Al-Li alloy; the cast aluminum alloy includes an Al-Si series, an Al-Cu series, an Al-Mg series or an Al-Zn series; the deformed aluminum alloy includes a 1xxx, 2xxx, 4xxx, 5xxx, 6xxx or 7xxx alloy; the ceramic particles in the ceramic / high entropy alloy composite particles include TiB2, TiC, TiN, SiC or ZrO2; the high entropy alloy particles include FeCoCrNi series, FeCoCrNiMn series, FeCoCrNiMo series, AlCoCrFeNi series, AlTiCrNiCu series, WTaMoNbV series or TiNbZrTa series.
3. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 2, characterized in that: In step (1), the mass fraction of the ceramic in the ceramic / high entropy alloy composite powder is between 0.5% and 50%, the mass fraction of the high entropy alloy is between 50% and 99.5%, and the sum of the two is equal to 1.
4. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, characterized in that: In step (1), the ceramic powder is flaky or other irregular shapes with a particle size of 0.05 to 1 μm, the high entropy alloy powder is spherical with a particle size of 1 to 100 μm, and the ceramic / high entropy alloy composite powder is spherical with a particle size of 1 to 100 μm.
5. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, characterized in that: In step (1), the mass fraction of the ceramic / high entropy alloy composite powder in the ceramic / high entropy alloy composite particle reinforcement phase is 1% to 10%, the mass fraction of the aluminum alloy matrix is 90% to 99%, and the sum of the two is equal to 1; the aluminum alloy powder is spherical and has a particle size of 1 to 100 μm.
6. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, characterized in that: In step (1), the ball milling time is 4 to 8 hours, the rotation speed is 120 to 220 rpm, the grinding balls are stainless steel balls or ZrO2 grinding balls, the grinding ball size is 2 to 6 mm, and the ball-to-material ratio is 5:1 to 10:1; the protective atmosphere is argon or nitrogen, and the product is dried in a vacuum environment at 70 to 120°C for 4 to 6 hours.
7. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, characterized in that: In step (2), the substrate used in the printing process is 1xxx, 2xxx, 4xxx, 5xxx, 6xxx, 7xxx aluminum alloy, and the substrate is preheated in a nitrogen or argon atmosphere at a temperature of 150°C to 200°C.
8. The laser additive manufacturing method of the ceramic / high entropy alloy composite particle reinforced aluminum-based composite material according to claim 1, characterized in that: In step (2), the laser power is 270W to 370W, the scanning speed is 1100mm / s to 1600mm / s, the powder layer thickness is 20 to 75μm, the scanning spacing is 110 to 150μm, and the scanning strategy is 67° interlayer rotation.
9. The aluminum-based composite material reinforced with ceramic / high entropy alloy composite particles according to claim 1, characterized in that: The ceramic / high entropy alloy composite powder described in step (1) is characterized by ceramic particles distributed inside and on the surface of the high entropy alloy powder, and the composite powder has good sphericity, surface smoothness and powder fluidity, and is suitable for the field of additive manufacturing.
10. The laser additive manufacturing method according to any one of claims 1 to 8 prepares a ceramic / high entropy alloy composite particle reinforced aluminum-based composite material.
Citation Information
Patent Citations
High-performance two-phase hybrid reinforced aluminum-based composite material and preparation method thereof
CN114350998A
Double-phase reinforced aluminum alloy and preparation method thereof
CN114645180A
Preparation method of high-strength and high-toughness aluminum-based composite material
CN118147474A
Three-level configuration high-entropy alloy particle reinforced aluminum-based composite material and preparation method thereof
CN118162623A
Metal-matrix composite based on high-entropy alloy
RU2793620C1
Cited By
Selective laser melting homogeneous powder and method for preparing composite material
CN121267200A
A method for selective laser melting of homogeneous powder and preparation of composite materials
CN121267200B
